2022
DOI: 10.1002/nop2.1430
|View full text |Cite
|
Sign up to set email alerts
|

Association of nursing hours with cognitive function, balance, and dependency level of stroke patients

Abstract: Aims To examine the association of nursing hours given to patients with stroke with clinical characteristics to predict the nursing care needs. Design Twenty‐four‐hour observational study Methods Nursing hours per patient day (NHPPD) of 171 stroke patients were measured by 146 nursing personnel who worked on the day of the observation. Cognitive function, balance ability and dependency level were assessed using the Korean version of the Mini‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…33 When nursing workloads are suitable, nurses have more time and ability to protect, prevent, promote, and dedicate themselves to enhancing nursing performance to ensure patient safety. 34 In addition, this result found that an average patient-tonurse ratio with a mean score of 8:1 was higher than the standard ratio of 4:1 in medical units, 5:1 in surgical and orthopedic units, and 6:1 in gynecological units. 35 The COVID-19 outbreak situation in Thailand might be a reason for the high nursing workload, especially the patient-to-nurse ratio in regional hospitals.…”
Section: Pacific Rim Int J Nurs Res • April-june 2024mentioning
confidence: 91%
See 2 more Smart Citations
“…33 When nursing workloads are suitable, nurses have more time and ability to protect, prevent, promote, and dedicate themselves to enhancing nursing performance to ensure patient safety. 34 In addition, this result found that an average patient-tonurse ratio with a mean score of 8:1 was higher than the standard ratio of 4:1 in medical units, 5:1 in surgical and orthopedic units, and 6:1 in gynecological units. 35 The COVID-19 outbreak situation in Thailand might be a reason for the high nursing workload, especially the patient-to-nurse ratio in regional hospitals.…”
Section: Pacific Rim Int J Nurs Res • April-june 2024mentioning
confidence: 91%
“…This result is congruous with a previous study that identified NHPPD as a crucial determinant influencing the nurses' performance in ensuring patient safety. 34 However, NHPPD was the least potent predictor affecting NPPS. It may be that NHPPD was calculated from the number of productive hours needed based on patient acuity in the patient classification system from all nursing staff to provide care per day for each patient on a given unit.…”
Section: Pacific Rim Int J Nurs Res • April-june 2024mentioning
confidence: 95%
See 1 more Smart Citation